The queen of cool - Castellucci, Cecil, 1969- (Cambridge, Mass. : Candlewick Press, 2006)
Bored with her life, popular high school junior Libby signs up for an internship at the zoo and discovers that the "science nerds" she meets there may have a few things to teach her about friendship and life.
Accelerated Reader AR
Keywords: Self-perception -- Fiction; Conduct of life -- Fiction; Zoos -- Fiction; High schools -- Fiction; Schools -- Fiction